Pharmacogenetics, Plasma Concentrations, Clinical Signs and EEG During Propofol Treatment. (19th July 2014) - Khan, Muhammad Suleman; Zetterlund, Eva‐Lena; Gréen, Henrik; Oscarsson, Anna; Zackrisson, Anna‐Lena; Svanborg, Eva; Lindholm, Maj‐Lis; Persson, Harald; Eintrei, Christina
Abstract A variety of techniques have been developed to monitor the depth of anaesthesia. Propofol's pharmacokinetics and response vary greatly, which might be explained by genetic polymorphisms. We investigated the impact of genetic variations on dosage, anaesthetic depth and recovery after total intravenous anaesthesia with propofol. A total of 101 patients were enrolled in the study. The plasma concentration of propofol during anaesthesia was measured using high‐performance liquid chromatography. EEG was monitored during the surgical procedure as a measure of anaesthetic depth. Pyrosequencing was used to determine genetic polymorphisms in CYP2B6, CYP2C9, the UGTIA9‐promotor and the GABRE gene. The correlation between genotype and to plasma concentration at the time of loss of consciousness (LOC), the total induction dose, the time to anaesthesia, eye opening and clearance were investigated. EEG monitoring showed that the majority of the patients had not reached a sufficient level of anaesthetic depth (subdelta) at the time of loss of consciousness despite a high induction dose of propofol. Patients with UGT1A9‐331C/T had a higher propofol clearance than those without (p = 0.03) and required a higher induction dose (p = 0.03). The patients with UGT1A9‐1818T/C required a longer time to LOC (p = 0.03). The patients with CYP2C9*2 had a higher concentration of propofol at the time of LOC (p = 0.02). The polymorphisms in the metabolizing enzymes and the receptor could not explain the large variation seen in the pharmacokinetics of propofol and the clinical response seen. At LOC, the patients showed a large difference in EEG pattern.